STANDARDIZATION OF YOGAAMRUTO RASA BY USING MODERN ANALYSIS TECHNIQUES - Dubey, *Somil; Deepti, Gubrele; Mohan Rao, G. Rama (International Journal of Ayurveda and Pharma Research, 2016)
Rasa Shastra is a partially independent branch of Ayurvedic medicine, which deals with preparation of the drugs with metals and minerals to produce the drugs with higher efficacy in lower dose with good palatability. Yogaamruto Rasa (YMR) is one such Rasoushadhi mentioned in Rasa Kamdhenu indicated for all types of Kushta. Parada, Gandhaka, Tamra churna, Vatsanabha, Vacha, Trikatu, Musta and Vidanga are the main ingredients of YMR. Shodhana, Mardana, Murchchana, Pishti nirmana, Aagni paaka are the important steps involved in preparation of YMR. Till date no standards are available for the above drug. Need of the hour is to revalidate the safety and efficacy of the above said formulation. In the current study of YMR it was subjected to analysis through X-ray diffraction (XRD), Scanning electron microscope (SEM), Energy dispersive X-ray spectroscopy (EDX) and Zeta potential (ZP). XRD of YMR reveals that major peaks are of Cu20 (Cuprite) and minor peaks of HgS (Meta Cinnabar), Cu2S (Cuprous Sulphide). SEM study found the smallest grain size ranging between115nm at 5Kx magnification to 82.11 nm at 7Kx magnification. EDX study reveals that YMR contains significant percentage of O-25.96%, Cu-22.82%, C-20.41%, Hg- 12.84 %, S- 9.8%. w/w. ZP mean value for YMR is 51.4 mV which indicates moderate colloidal stability.